Accumulating Foreign Reserves Under Floating Exchange Rates - Goncalves, Fernando M. (Washington, D.C. : International Monetary Fund, 2008)
Official accumulation of foreign reserves may be perceived as interventions to influence the exchange rate, undermining the credibility of floating exchange rates and inflation targets. This paper develops a theoretical framework to study the interaction between reserve accumulation and monetary policy. The model uncovers a trade-off between the speed of reserve accumulation and anti-inflationary credibility. Under reasonable assumptions, delegation of intervention and monetary policy decisions to separate government agencies allows faster reserve accumulation, while centralization of these decisions results in a more stable economy. The analysis underscores the importance of rather overlooked institutional features of policymaking in open economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet